2016
DOI: 10.5152/turkjorthod.2016.15-00017r1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Photography Trends in Orthodontics

Abstract: The use of photographic documentation is essential procedure in orthodontic diagnosis and treatment planning. These records are also required for legal protection. Digital technology is gaining importance for creation of photographic recording. In this article, we want to give an overview of standardization and the latest developments in the photographic field in orthodontic clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Dental fotoğraflama, diş hekimlerinin gerçekleştirilen tedaviye yönelik önemli aşamaları kayıt altına almalarına olanak sağlamanın yanında ortodonti disiplinine hastalarla iletişim, uzmanın kendini değerlendirebilmesi, tedavi planlaması, bilimsel araştırmalar için veri sağlama, eğitim ve hatta pazarlamaya kadar birçok alanda katkı sağlamaktadır. [16][17][18][19][20] Bu alanda özellikle kullanılan dijital teknolojilere odaklanan bilimsel çalışmalar olmasına karşın, bu teknolojilerin klinik ortama uyumu ve hasta ve hekim deneyimleri açısından değerlendirilmesine ilişkin bir çalışmaya literatürde rastlanmamıştır. Bu araştırma, 16-20 yaşları arasında 20 hastanın ve 12 uzmanın, ortodonti tedavisinin başında uygulanan dental fotoğraflama süreci konusundaki görüşlerine odaklanan, daha önce Cifter (2018) ve Altıparmakoğulları ve diğ (2017) tarafından yayımlanmış olan iki ayrı kalitatif gözlem ve mülakat çalışması verileri değerlendirilerek başlamıştır.…”
Section: Discussionunclassified
“…Dental fotoğraflama, diş hekimlerinin gerçekleştirilen tedaviye yönelik önemli aşamaları kayıt altına almalarına olanak sağlamanın yanında ortodonti disiplinine hastalarla iletişim, uzmanın kendini değerlendirebilmesi, tedavi planlaması, bilimsel araştırmalar için veri sağlama, eğitim ve hatta pazarlamaya kadar birçok alanda katkı sağlamaktadır. [16][17][18][19][20] Bu alanda özellikle kullanılan dijital teknolojilere odaklanan bilimsel çalışmalar olmasına karşın, bu teknolojilerin klinik ortama uyumu ve hasta ve hekim deneyimleri açısından değerlendirilmesine ilişkin bir çalışmaya literatürde rastlanmamıştır. Bu araştırma, 16-20 yaşları arasında 20 hastanın ve 12 uzmanın, ortodonti tedavisinin başında uygulanan dental fotoğraflama süreci konusundaki görüşlerine odaklanan, daha önce Cifter (2018) ve Altıparmakoğulları ve diğ (2017) tarafından yayımlanmış olan iki ayrı kalitatif gözlem ve mülakat çalışması verileri değerlendirilerek başlamıştır.…”
Section: Discussionunclassified
“…DDP enables clinicians to record key stages of treatment. It also contributes to the orthodontic discipline in aspects including communication with patients, self-check of specialists, treatment planning, and provision of the treatment for clinical research, education, and marketing purposes to increase the patient's motivation and cooperation during the process [ 1 5 ]. Medicolegal concerns are another aspect, and DDP protects both patients' and dentists' rights in possibly difficult circumstances [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relevant literature on DDP primarily focuses on the technological aspects of the procedure and their possible influences on picture quality [ 1 , 3 , 5 , 8 ]. No prior research has been identified regarding the components and their effects on the patient's experience.…”
Section: Introductionmentioning
confidence: 99%